Sensory Perception of Material Texture in Consumer Products. (3rd May 2016) - Zuo, Hengfeng; Jones, Mark; Hope, Tony; Jones, Robin
Abstract: A more informed understanding of information about human sensory perception of materials is playing an increasingly important role in the selection and combination of materials within manufactured products. An initial perception of a product may be based on sensory properties such as colour, texture, sound, smell, and taste. Designers use textures within most of their design practices and understand that texture and texture combination can have a strong visual and tactile impact. The visual aesthetics of a particular material and the surface texture information are signalled through visual and tactile feedback. This contributes to how the user perceives the 'material representation' (which is defined as: the perceived images, properties, meanings, and values of a material in the human–product interface under a specific set of environmental conditions). Prior scholarship is limited with regard to information about the sensory and aesthetic characteristics of materials. Hence previous work reported by the authors of this paper has focused mainly on material texture through visual and tactile feedback. By carrying out controlled experimental research on texture, using specially prepared material samples, a dimension–lexicon system was used to subjectively describe a material texture by touch. Slight differences in the descriptive lexicons used were analysed in terms of gender, material surface finish, sensory conditions, and control groups. Further research revealed correlations between various subjective responses within the texture perception dimensions. In parallel, through experimental testing, the quantitative relationships between subjective response to texture and the objective physical parameters of materials were also reported. An understanding of these correlations assisted in the selection of better-matching material texture combinations. In this work the application of previous research results in design practice has been achieved as a result of collaboration with a leading UK manufacturer of hairdryers. Contextual research on material sensory perception and its influence on the whole product has been undertaken. This paper introduces the research methodology, the research results, and discussion from this research. Five typical hairdryers of the same brand varied in materials and textures were selected as product samples to be operated and evaluated by 25 participants, under controlled visual–touch conditions, simulating a typical operating process for the product. The contents of evaluation covered the sensory, functional, emotional, and associative responses to the whole product but with focus on the handle for each hairdryer. The relationship between these responses is discussed, the influencing factors for a good handle (e.g. comfort) are analysed, and suitable materials/textures are suggested. The results not only provide recommendations for further improvement and development of the products for our collaborative company, but also give insights on materials/texture selection for a wider range of consumer products where handle grip and perceived comfort and control are important factors for creating a positive user experience.